PENGARUH KEPERCAYAAN DIRI DAN REWARD TERHADAP KINERJA GURU SD NEGERI KECAMATAN LANGGAM KABUPATEN PELALAWAN - Selvina Beti; Azhar Azhar; Rita Kurnia (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2022)
This research aims to determine the influence of confidence and rewards on the performance of elementary school teachers in Langgam District, Pelalawan Regency, both simultaneously and partially. The population in this study was 269 people, while the study sample was 161 people. The data analysis used is regression analysis, regression coefficient, and determination coefficient. The results showed that in silmultan there was a negative influence of confidence (X1) and reward (X2) on teacher performance (Y) of 72.7%. While partial confidence (X1) negatively affects teacher performance (Y) by 48.5%, and reward (X2) negatively affects teacher performance by 4.5%. It can be concluded that confidence and reward (X2) together have a negative effect on the performance (Y) of elementary school teachers in Langgam District, Pelalawan Regency in a strong category.